2014
DOI: 10.1117/1.jatis.1.1.014005
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube optical mirrors

Abstract: Abstract. We report the fabrication of imaging quality optical mirrors with smooth surfaces using carbon nanotubes (CNT) embedded in an epoxy matrix. CNT/epoxy is a multifunctional composite material that has sensing capabilities and can be made to incorporate self-actuation. Moreover, as the precursor is a low density liquid, large and lightweight mirrors can be fabricated by processes such as replication, spincasting, and three-dimensional printing. Therefore, the technology holds promise for the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Tunable mirrors based on smart materials were developed (left side in Figure 43). [85] Imaging-quality optical mirrors have been developed by using carbon nanotubes embedded in an epoxy matrix (CNT/E). The development is notable in two ways.…”
Section: Iii-3 Tunable Mirrors and Filtersmentioning
confidence: 99%
See 1 more Smart Citation
“…Tunable mirrors based on smart materials were developed (left side in Figure 43). [85] Imaging-quality optical mirrors have been developed by using carbon nanotubes embedded in an epoxy matrix (CNT/E). The development is notable in two ways.…”
Section: Iii-3 Tunable Mirrors and Filtersmentioning
confidence: 99%
“…In the 1990s, developers adopted active optics for large telescopes, and the current generation uses thin, flexible mirrors that maintain their shape by a system of external actuators that push and pull on the surface. Tunable mirrors based on smart materials were developed (left side in figure 43) [84]. Imaging-quality optical mirrors have been developed by using CNTs embedded in an epoxy matrix (CNT/E).…”
Section: Tunable Mirrors and Filtersmentioning
confidence: 99%
“…Spitzer observed 55 Cnc e multiple times, revealing a significant variability in the occultation depth between 2012 and 2013 (Demory et al 2015) that was later confirmed by Tamburo et al (2018). However, a recent analysis using the Transiting Exoplanet Survey Satellite (TESS) (Ricker et al 2014) observations indicated weak evidence of variability in the occultation depth in the optical range across the sectors (Meier Valdés et al 2022).…”
Section: Introductionmentioning
confidence: 98%
“…When transferred efficiently to the composite, they are expected to provide mechanical improvements (strength, stiffness, interlaminar shear strength) and enhance the thermal and electrical properties [15,16]. Chen and Rabin [17] showed that it is possible to produce epoxy/CNT composites with surface optical quality to be used as mirrors using the replica method. Kia [18] has patented a method for reducing the fiber print-through in composites reinforced with long fibers with the addition of CNT.…”
Section: Introductionmentioning
confidence: 99%